Relevance and Transformation of Pesantren Educational Management in the Disruption Era: A Contemporary Organizational Perspective - Miftahul Hadi (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2025)
This study examines the relevance and transformation of the management paradigm of pesantren education in the era of disruption through the perspective of contemporary organizational theory. The research aims to evaluate the degree of relevance of traditional pesantren management paradigms within the context of digital transformation and institutional modernization, identify conceptual weaknesses that limit organizational adaptability and formulate a transformative managerial framework grounded in contemporary organizational theories. This research employs a qualitative approach with a literature-based analytical design combined with conceptual analysis. Data were collected from recent scholarly publications, policy documents, and authoritative works on Islamic educational management and organizational theory published within the last five years. The analysis was conducted through interpretive synthesis and critical mapping to uncover patterns of paradigm continuity, structural rigidity, and emerging adaptive strategies within pesantren institutions. The findings reveal that pesantren management remains highly resilient due to its value-based leadership, communal culture, and moral authority structure. However, several conceptual constraints persist, particularly in hierarchical decision-making centralization, limited institutional digital governance models, and insufficient integration of strategic management principles. These weaknesses reduce organizational agility in responding to technological disruption, regulatory demands, and generational shifts among students. The study proposes a transformative managerial framework that integrates adaptive leadership, organizational learning, digital governance, and value-based strategic management. This framework allows pesantren to preserve their foundational identity while enhancing institutional responsiveness and innovation capacity.